Management of Irritable Bowel Syndrome: Novel Approaches to the Pharmacology of Gut Motility - Carmelo Scarpignato; Iva Pelosini (Canadian Journal of Gastroenterology)
Although it is unclear to what extent irritable bowel syndrome (IBS) symptoms represent a normal perception of abnormal function or an abnormal perception of normal function, many believe that IBS constitutes the clinical expression of an underlying motility disorder, affecting primarily the mid- and lower gut. Indeed, transit and contractile abnormalities have been demonstrated with sophisticated techniques in a subset of patients with IBS. As a consequence, drugs affecting gastrointestinal (GI) motility have been widely employed with the aim of correcting the major IBS manifestations, ie, pain and altered bowel function. Unfortunately, no single drug has proven to be effective in treating IBS symptom complex. In addition, the use of some medications has often been associated with unpleasant side effects. Therefore, the search for a truly effective and safe drug to control motility disturbances in IBS continues. Several classes of drugs look promising and are under evaluation. Among the motor- inhibiting drugs, gut selective muscarinic antagonists (such as zamifenacin and darifenacin), neurokinin2 antagonists (such as MEN-10627 and MEN-11420), beta3-adrenoreceptor agonists (eg, SR-58611A) and GI-selective calcium channel blockers (eg, pinaverium bromide and octylonium) are able to decrease painful contractile activity in the gut (antispasmodic effect), without significantly affecting other body functions. Novel mechanisms to stimulate GI motility and transit include blockade of cholecystokinin (CCK)A receptors and stimulation of motilin receptors. Loxiglumide (and its dextroisomer, dexloxiglumide) is the only CCKA receptor antagonist that is being evaluated clinically. This drug accelerates gastric emptying and colonic transit, thereby increasing the number of bowel movements in patients with chronic constipation. It is also able to reduce visceral perception. Erythromycin and related 14-member macrolide compounds inhibit the binding of motilin to its receptors on GI smooth muscle and, therefore, act as motilin agonists. This antibiotic accelerates gastric emptying and shortens orocecal transit time. In the large bowel a significant decrease in transit is observed only in the right colon, which suggests a shift in fecal distribution. Several ‘motilinomimetics’ have been synthesized. Their development depends on the lack of antimicrobial activity and the absence of fading of the prokinetic effect during prolonged administration. 5-hydroxytryptamine (5-HT)4 agonists with significant pharmacological effects on the mid- and distal gut (such as prucalopride and tegaserod) are available for human use. These ‘enterokinetic’ compounds are useful for treating constipation- predominant IBS patients. 5-HT3 receptor antagonists also possess a number of interesting pharmacological properties that may make them suitable for treatment of IBS. Besides decreasing colonic sensitivity to distension, these drugs prolong intestinal transit and may be particularly useful in diarrhea-predominant IBS. Finally, when administered in small pulsed doses, octreotide, besides reducing the perception of rectal distension, accelerates intestinal transit, although other evidence disputes such an effect.